Assessing EU leadership on climate change: the limits of diffusion in EU relations with China and India - Torney, Diarmuid (2012)
Abstract: The EU has for a long time claimed the title of “leader” in the international politics of climate change. However, existing research has generally failed to specify whether the EU’s purported leadership has induced the “followership” of other states. This working paper seeks to shed light on this somewhat neglected topic by examining the attempted diffusion of climate change norms, policies, and institutions by the EU to China and India. The paper makes two principal arguments. First, the development of Chinese and Indian climate change policy should be understood as primarily domestic developments. Nonetheless, there was limited evidence of diffusion from the EU, but there was significant variation between the Chinese and Indian responses to the EU’s diffusion attempts. The Chinese response was one increasing accommodation; the Indian response was a more straightforward case of resistance. Second, domestic factors help to explain the variation in the Chinese and Indian responses t